PERAN FUNGSI MANAJERIAL DALAM MENDUKUNG PELAYANAN ADMINISTRASI PERKANTORAN MODERN - Jumalia Mannayong; Rudi Salam (Politeknik STIA LAN Makassar, 2021)
Service excellence is the dream of all service recipients. Therefore, efforts to make it happen requires a stable managerial role in the organization. The research objective was to determine the role of managerial functions in supporting modern office administration services at the Barombong District office in Gowa Regency. Research respondents were 100 people who had received services. Data collection techniques through observation, questionnaires, interviews with service providers (employees) and service recipients (community), documentation. In carrying out their main duties and functions as an employee at the Barombong District Office in Gowa Regency, they have shown seriousness in providing services to the community. This can be seen from the commitment of employees in providing excellent service to the community receiving services. of several service criteria delivered, namely: 1) frequency of assignment of officers to the requirements, costs and time of administrative completion, 2) Timeliness of Administrative Officers in Providing Services, and 3) Officers make the best use of service time.